Engagement in and Benefits of a Short-Term, Brief Psychotherapy Intervention for PTSD During Pregnancy - Kornfield, Sara L.; Johnson, Rachel L.; Hantsoo, Liisa V.; Kaminsky, Rachel B.; Waller, Rebecca; Sammel, Mary; Epperson, C. Neill (Frontiers in Psychiatry, 2022)
ABSTRACT (238 words) Trauma-related symptoms and posttraumatic stress disorder (PTSD) are common during pregnancy and have adverse effects on pregnancy and birth outcomes, postpartum maternal mental health, and child development. The arousal symptoms associated with PTSD, including heightened or dysregulated physiology, may contribute to these adverse outcomes. Low-income minoritized women may be at highest risk given more lifetime exposure to trauma and limited access to mental health care. While evidence-based psychotherapies for PTSD exist, none are targeted to non- treatment seeking individuals nor specifically integrated with prenatal care. Thus, we developed and tested the efficacy of a short-term (4 sessions) brief (30-45 minute) psychotherapeutic intervention designed to address PTSD symptoms in pregnant women receiving prenatal care at two urban medical centers. Participants were 32 pregnant women with an average gestational age of 18.5 weeks at the time of enrollment. The sample was overwhelmingly non-Caucasian, single, and reported very low income. Participants completed measures of trauma-related symptoms (Posttraumatic Stress Disorder Checklist, PCL), and depression (Edinburgh postnatal Depression Scale, EPDS) at baseline, twice during treatment, post-treatment, and at 10-14 weeks postpartum. The intervention was successful at significantly decreasing symptoms of PTSD (PCL score = -20.27, 95% CI: -25.62, -14.92, p < 0.001, W = -7.43) and depression (EPDS score = -4.81, 95% CI:-7.55, -2.06, p = 0.001, W = -3.23) by the final session. These benefits were sustained at post-treatment and postpartum follow ups. Future research should further explore the effectiveness of this treatment in a randomized controlled trial.